The reservoir system for Trypanosoma (Kinetoplastida, Trypanosomatidae) species in large neotropical wetland - Santos, Filipe Martins; Barreto, Wanessa Texeira Gomes; de Macedo, Gabriel Carvalho; Barros, Juliana Helena da Silva; Xavier, Samanta Cristina das Chagas; Garcia, Carolina Martins; Mourão, Guilherme; de Oliveira, Jader [UNESP]; Rimoldi, Aline Ribeiro [UNESP]; Porfírio, Grasiela Edith de Oliveira; de Andrade, Gisele Braziliano; Perles, Lívia [UNESP]; et al. (Elsevier, 2019)
Distinct species of Trypanosoma have been documented sharing the same hosts in different environments in intricate transmission networks. Knowing this, this study investigated the role of different hosts in the transmission cycles of Trypanosoma species in the Pantanal biome. The mammals were sampled from November 2015 to October 2016. We sampled a total of 272 wild mammals from 27 species belonging to six orders and 15 families, and three species of triatomines (n = 7). We found high parasitemias by Hemoculture test for Trypanosoma cruzi (TcI), Trypanosoma rangeli, Trypanosoma cruzi marinkellei and Trypanosoma dionisii, and high parasitemias by Microhematocrit Centrifuge Technique for Trypanosoma evansi. The carnivore Nasua nasua is a key host in the transmission cycles since it displayed high parasitemias for T. cruzi, T. evansi and T. rangeli. This is the first report of high parasitemias in Tamandua tetradactyla and cryptic infection in Dasypus novemcinctus by T. cruzi; cryptic infection by T. evansi in Eira barbara, Euphractus sexcinctus and Dasyprocta azarae. The collection of Panstrongylus geniculatus increased the geographic distribution of this vector species in the South America. Our results indicate that Trypanosoma species circulate in a complex reservoir system including different host species with different infective competences.
Keywords: Free-living mammals; Triatominae; Trypanosoma cruzi; Trypanosoma cruzi marinkellei; Trypanosoma dionisii; Trypanosoma evansi; Trypanosoma rangeli